Cibalackrot‐type compounds: Stable singlet fission materials with aromatic ground state and excited state. (17th October 2022) - Zeng, Weixuan; Szczepanik, Dariusz W.; Bronstein, Hugo
Abstract: Singlet fission is a multiexciton generation process, where one singlet exciton is absorbed and two triplet excitons are produced. The potential of more efficient photovoltaic devices utilizing singlet fission materials has attracted wide interests for tuneable, stable organic chromophores with suitable excited‐state ordering. The strict energetic requirements hinder the exploration of novel organic materials, and most well‐known singlet fission materials, linear acenes, are considered to be unstable in their excited states. To solve the stability issue, excited‐state aromaticity provides a feasible research option, from which a few chromophores have been designed and studied. This review describes indolonaphthyridine (IND) derivative chromophores and discusses their ability to undergo singlet fission with superior ambient stability. Deepened theoretical analysis taking into account the excited‐state Hückel‐aromatic and diradical characters rationalizes the special properties of these chromophores. Moreover, the improved understanding of the aromatic character enables us to outline a feasible design strategy suitable for other scaffolds undergo singlet fission and excited‐state aromaticity. Hopefully, this review can light a fire on the way toward various novel singlet fission chromophores designed based on the excited‐state aromatic view. Abstract : This mini review summarizes a series of photostable singlet fission compounds sharing similar framework benefited from aromaticity in both ground and excite state. In these scaffolds, Hückel‐, instead of Baird, aromatic units contribute as locks for the high photostability. The unpaired electrons are delocalized mainly through the central core and can be manipulated with conjugated extension on various substituents. The understanding outlines a design approach for tuning the excited state energy level and seeking new singlet fission candidates.